2014
DOI: 10.4314/afrrev.v8i2.16
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Style and Primary School Pupils’ Reading Achievement in South-Western Nigeria

Abstract: Scholars outside Africa have acknowledged the influence of parenting styles on children's academic achievement in general and language achievement in particular but such studies are inconclusive as they came up with conflicting findings. It is in line with this trend that this ex-post facto research investigated the impact of parenting style in Primary school pupils' Reading Achievement in SouthWestern Nigeria. The study involved 2400 primary five pupils form 20 randomly sampled public primary schools in South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…The finding of this study which disclosed authoritative parenting style being the most experienced parenting styles among the students resonates with Nwokocha et al, (2017) and Kiran, Farooqi and Ahmed's (2018) results which revealed that the most commonest and dominant parenting styles experienced by students was authoritative parenting style than authoritarian, permissive and uninvolved parenting styles. Contrarily, the findings of this study from research question one disagrees with Fakeye's (2014) study which indicated that the authoritarian parenting style was the most dominant parenting style experienced by students.…”
Section: Discussion Of the Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The finding of this study which disclosed authoritative parenting style being the most experienced parenting styles among the students resonates with Nwokocha et al, (2017) and Kiran, Farooqi and Ahmed's (2018) results which revealed that the most commonest and dominant parenting styles experienced by students was authoritative parenting style than authoritarian, permissive and uninvolved parenting styles. Contrarily, the findings of this study from research question one disagrees with Fakeye's (2014) study which indicated that the authoritarian parenting style was the most dominant parenting style experienced by students.…”
Section: Discussion Of the Resultscontrasting
confidence: 99%
“…In another study, Kiran, Farooqi and Ahmed (2018) investigated the parenting style and anti-social behavior among students in secondary schools in Okara, Pakistan and unveiled that parents use authoritative parenting more than authoritarian and permissive parenting styles being the least parenting style in rearing their children. Fakeye (2014) did an assessment of the nature of parenting styles experienced by Primary School pupils in South-Western Nigeria and discovered that Primary School pupils experienced Authoritative parenting styles more than uninvolved, permissive with the least being authoritarian parenting styles. In Ghana, Owusu-Gyan (2013) studied the impact of parenting styles on the personal and social development of children at Elmina, and it was revealed that the majority of parents in Elmina used authoritative parenting styles with the least being permissive and uninvolving parenting styles.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, recent empirical studies on parenting styles focus on its influence on problem behaviour (Maliki & Inokoba, 2011;Tunde-Ayinmode & Adegunloye;Omolola, 2011;Akanbi & Oyewo, 2013;Umo, 2013) while a few that addressed its relationship with students' academic achievement were done at the primary school level (Fakeye, 2008;Shobola, Omoregbe, & Olufemi, 2012). Although Ogunleye, Omirin, and Balogun (2013) examined the influence of parenting style on secondary school students' academic achievement using a small sample of secondary school students in one school, there is need to not only extend this study but also ascertain whether the influence of parenting style on academic achievement is more direct or mediated by students' achievement goal orientation.…”
mentioning
confidence: 99%